(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the essence and content of the concepts of equality and equation as essential components of the mathematics curriculum, as well as the methodological foundations for teaching them. Theoretical aspects such as true and false equalities, the concept of an equation as an equality containing an unknown, the root of an equation, and equivalent equations are consistently presented. In addition, the main properties of true equalities and their practical applications are analyzed through examples. The paper also explains step-by-step methods for solving equations and proposes methodological approaches aimed at developing students’ logical thinking and mathematical reasoning.